2021
DOI: 10.1186/s12888-020-03027-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress among Italians during the 2019 coronavirus disease (COVID-19) quarantine

Abstract: Background Quarantine as a preventive action to reduce people’s exposure to a contagious disease has substantial psychological impact. We aimed to collect information on psychologically distressing experiences of Italians living in quarantine during the COVID-19 pandemic. Methods From 6 to 20 April 2020 participants filled out an online questionnaire. Demographic and physical symptoms data from the prior 14 days of quarantine were collected. Psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
42
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 55 publications
10
42
3
1
Order By: Relevance
“…Furthermore, we found gender differences in the mild/moderate distress range (17.92% and 82.07% for men and women, respectively) and the severe distress range (7.26% and 92.73% for men and women, respectively). These findings are in line with those obtained by other studies using the CPDI [ 9 , 23 , 24 , 25 , 26 , 27 ]. Furthermore, studies using instruments other than the CPDI to measure stress symptoms reported similar findings, with women experiencing higher levels of psychological distress than men [ 8 , 13 , 15 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, we found gender differences in the mild/moderate distress range (17.92% and 82.07% for men and women, respectively) and the severe distress range (7.26% and 92.73% for men and women, respectively). These findings are in line with those obtained by other studies using the CPDI [ 9 , 23 , 24 , 25 , 26 , 27 ]. Furthermore, studies using instruments other than the CPDI to measure stress symptoms reported similar findings, with women experiencing higher levels of psychological distress than men [ 8 , 13 , 15 , 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…Overall, it seems that being female constitutes an important risk factor for developing COVID-related stress symptoms. A recent Italian large-scale study with 20,158 participants found that higher CPDI scores were significantly associated with gender, being two-fold in women in comparison to men [ 25 ]. Similar results were found in Chinese [ 9 ], Brazilian [ 26 ], and Bangladeshi [ 27 ] samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher stress levels associated with lockdown measures were observed in some groups, such as women [185][186][187] (particularly pregnant women 188,189 ), single/divorced adults 81 , older people (particularly with pre-existing mental health conditions 175,190 ), parents with young children 191 , university students and young adults [192][193][194] , workers 195 , those self-medicating 196 , the economically deprived 143 , those with pre-existing depression 197 , bipolar disorders 198 , and other chronic medical conditions 139,189,[199][200][201] . A large study of 56,679 participants in China found that quarantine had a profound effect on the mental health of specific vulnerable groups, including those with pre-existing mental disorders, chronic physical diseases, frontline workers, and those living in the most affected areas 202 .…”
Section: Stressmentioning
confidence: 98%
“…Based on recent expertise during the pandemic [ 21 , 22 ], the survey was organized and managed according to previous methods used in survey studies by the authors. The present study aimed to investigate the psychological impact of the pandemic on front-line staff working at the new COVID-19 ward at Milano Fiera, Lombardy during the second pandemic wave.…”
Section: Introductionmentioning
confidence: 99%